2007
DOI: 10.4103/1596-3519.55718
|View full text |Cite
|
Sign up to set email alerts
|

Management of hyperglycaemic emergencies in the tropics

Abstract: Diabetic ketoacidosis (DKA) and hyperglycaemic hyperosmolar state are the two most serious acute metabolic complications of diabetes even if managed properly. These disorders can occur in both types 1and 2 diabetes, and remain an important cause of morbidity and mortality in diabetic populations especially, in the developing countries. Intravenous insulin and fluid replacement are the mainstays of therapy, with careful monitoring of potassium levels. Bicarbonate therapy is rarely needed. Infection, omission of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Otherwise, this non-compliance rate is not acceptable and hence patient education, improvement in accessibility of nearby health facilities that provide medical care for diabetics and economic empowerment of DM patients may be warranted. It has been reported [ 27 , 31 ] that stopping insulin for economic reasons, unavailability and unaffordability of insulin, missed clinics, perceived ill-health and alternative therapies like herbs, prayers and rituals are common problems that contributed to non-compliance to antidiabetic medications in the Tropical and Sub-Saharan African diabetic patients.…”
Section: Discussionmentioning
confidence: 99%
“…Otherwise, this non-compliance rate is not acceptable and hence patient education, improvement in accessibility of nearby health facilities that provide medical care for diabetics and economic empowerment of DM patients may be warranted. It has been reported [ 27 , 31 ] that stopping insulin for economic reasons, unavailability and unaffordability of insulin, missed clinics, perceived ill-health and alternative therapies like herbs, prayers and rituals are common problems that contributed to non-compliance to antidiabetic medications in the Tropical and Sub-Saharan African diabetic patients.…”
Section: Discussionmentioning
confidence: 99%
“…Another study by Kitabchi and Nyenwe7 in the US showed a declining mortality rate in patients with DKA compared with HHNK, which remained alarmingly high. In Nigeria, hyperglycemic emergencies are an important cause of morbidity and mortality due to poor drug compliance, and this may be attributed to poverty, ignorance, poor health education, infection, delayed diagnosis and treatment, lack of access to medical care, erratic supply of essential drugs, cultural and religious beliefs, poor laboratory support, and less emphasis on electrolyte monitoring, especially potassium 8–11…”
Section: Introductionmentioning
confidence: 99%
“…The comparatively higher percentage of known DM patients on treatment in our study might explain this disparity. The nancial hitches and unjust traditional tenets have been linked with missed insulin doses and antidiabetic medication discontinuation among Tropical and Sub-Saharan African DM patients (32,33). Hence, it would be matter-of-factly to devise strategies to ensure accessible standard DM care in the region and abate the dreadful consequences of noncompliance.…”
Section: Discussionmentioning
confidence: 99%